1979
DOI: 10.3758/bf03196944
|View full text |Cite
|
Sign up to set email alerts
|

Processing of text containing artificial inclusion relations

Abstract: The present studies were based on the hypothesis that the majority of college students have available to them the appropriate schema for understanding set inclusion relations, but that various factors influence the likelihood that the schema is used in the processing of text containing artificial inclusion relations. Although group data did not support this hypothesis. the data of individual subjects could be readily interpreted as resulting from the selection of one of a small set of representational schemata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
27
0

Year Published

1982
1982
2000
2000

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(31 citation statements)
references
References 16 publications
4
27
0
Order By: Relevance
“…Another way of looking at the data from this experiment is in terms of the strategies that subjects adopted (classified according to the criteria suggested by Mynatt & Smith, 1979). The results illustrate quite forcibly the points that have already emerged: strategies involving symmetry were more frequent than those involving asymmetry, and strategies involving transitivity were more frequent than those involving intransitivity.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Another way of looking at the data from this experiment is in terms of the strategies that subjects adopted (classified according to the criteria suggested by Mynatt & Smith, 1979). The results illustrate quite forcibly the points that have already emerged: strategies involving symmetry were more frequent than those involving asymmetry, and strategies involving transitivity were more frequent than those involving intransitivity.…”
Section: Resultsmentioning
confidence: 92%
“…Potts (1978) suggested that set inclusions were misinterpreted as similarity relationships; Mynatt and Smith (1979) suggested that they cued in an inappropriate processing schema; and Newstead and Griggs (1984) argued that erCopyright 1986 Psychonomic Society, Inc. rors might result from the quantifier all being interpreted fuzzily and thus allowing the occasional exception. None of these interpretational explanations has attracted widespread support, so it seems reasonable to explore in more detail the explanation in terms of response bias.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent experimental testing of this paradigm has confirmed the existence of these two phenomena (Carroll & Kammann, 1977;Griggs, 1976;Griggs & Osterman, 1980;Griggs & Warner, 1982;Mynatt & Smith, 1979;Newstead & Griggs, 1984;Newstead, Keeble, & Manktelow, 1985;Potts, 1976) despite the fact that considerable interparticipant differences have been identified (Griggs & Osterman, 1980;Mynatt & Smith, 1979). Experimenters have proposed two interpretations designed to account for the poor performance displayed in hierarchical inclusion tasks.…”
mentioning
confidence: 88%
“…Potts (1978) suggested that set inclusions are incorrectly treated as similarity relations, which are nontransitive and convertible; however, he provided no persuasive argument as to why set inclusions should be so misinterpreted. Mynatt and Smith (1979) claimed that the errors are due to inappropriate schema cuing; they claimed that subjects can process inclusions appropriately, for example, if these involve geographical or topographical inclusions (e.g., A is in B). However, the normal set inclusion using the quantifier all leads to inappropriate processing, although the authors gave no sound reason why this should occur.…”
mentioning
confidence: 99%